MENGGUNAKAN “MEME” DALAM WORD OF MOUTH (WOM) UNTUK MENINGKATKAN BRAND AWARENESS - Miyume Renata (Kompetensi (Competence : Journal of Management Studies), 2014)
Technologies are increasingly sophisticated, making a lot of people use the internet to communicate. Now, word of mouth communication does not have to meet face to face but can be done through viral marketing or via the internet. Viral marketingcan attract consumersthrough the Internetsuch aspicturesandvideos.Today, viral marketing is popular with meme. Meme is a unique idea in the form of pictures, videos, hashtags, and so on. With the popularity of memes, word of mouth communication may vary and further increase consumer brand awareness.